The effect of new business formation on employment: the dominance of density - Alexandra Schröter (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
Empirical analyses show that the employment effects of start-ups are highest in agglomerations, whereas moderately congested areas exhibit only modest effects, and weak or even no significant effects could be found in rural regions. This paper will set out to show that these discrepancies arise from specific characteristics of urban areas. The magnitude of the employment effects of entry in agglomerations can, therefore, be regarded as a further kind of agglomeration benefit which has not been discussed in the literature yet. In particular, it is explained how the distinct characteristics of urban areas contribute to the emergence of high-quality start-ups that are known to cause larger employment effects than other types of new businesses. In addition, this paper argues that the relatively intense competition in urban areas further stimulates the economic effects of new business formation in agglomerations.
Keywords: M13; O1; O18; R11; 330; Entrepreneurship; new business formation; regional development; entrepreneurship policy; Unternehmensgründung; Unternehmer; Beschäftigungseffekt; Regionale Konzentration; Agglomerationseffekt; Unternehmer; Regionale Entwicklung; Standortfaktor